Patient Experience with Rechargeable Implantable Pulse Generator Deep Brain Stimulation for Movement Disorders - Mitchell, Kyle T. (Stereotact Funct Neurosurg, 2019)
BACKGROUND/AIMS: Nonrechargeable deep brain stimulation implantable pulse generators (IPGs) for movement disorders require surgical replacement every few years due to battery depletion. Rechargeable IPGs reduce frequency of replacement surgeries and inherent risks of complications but require frequent recharging. Here, we evaluate patient experience with rechargeable IPGs and define predictive characteristics for higher satisfaction. METHODS: We contacted all patients implanted with rechargeable IPGs at a single center in a survey-based study. We analyzed patient satisfaction with respect to age, diagnosis, target, charging duration, and body mass index. We tabulated hardware-related adverse events. RESULTS: Dystonia patients had significantly higher satisfaction than Parkinson’s disease patients in re-charging, display, programmer, and training domains. Common positive responses were “fewer surgeries” and “small size.” Common negative responses were “difficulty finding the right position to recharge” and “need to recharge every day.” Hardware-related adverse events occurred in 21 of 59 participants. CONCLUSION: Patient experience with rechargeable IPGs was largely positive; however, frustrations with re-charging and adverse events were common. Dystonia diagnosis was most predictive of high satisfaction across multiple categories, potentially related to expected long disease duration with need for numerous IPG replacements.